Experiment study of ATP system for free-space optical communications - 肖永军 刘彦飞 董冉 熊准 (Optoelectronics letters, 2011)
To meet the requirement of high tracking angular accuracy for the acquisition, tracking, and pointing （ATP） subsystem of the free-space optical communication, and provide the basis for the further optical communication between maritime mobile platforms, the experimental system, which executing part for the fine tracking is voice coil motor with high frequency and good performance for error compensation, is established, and the whole system can be controlled by personal computer. A series of experiments has been done for the simulation target of different uniform speed, and the data of tracking error for fine tracking and coarse tracking are collected, analyzed and evaluateds separately, and the real-time optical power of communication laser is also collected. The result shows that standard deviation for ATP system tracking error increases with the increase of target speed, while the range of tracking error appears to be no order. Furthermore, communication link can be hold for a long time.